2016
DOI: 10.1177/0040517516654109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction and experimental analysis of ends-together yarn splicing

Abstract: 3Pneumatic yarn splicing is a technical process for joining two yarn ends together. The 4 process involves injecting compressed air into a splicing chamber. Inlet pressure and 5 chambers slope determine the main parameters affecting this process. In this paper, large 6 eddy simulation (LES) of the flow field in four selected splicing chambers is carried out. 7The chambers are used for splicing ends-together yarns. The results of these simulations are 8 analysed to investigate first the effects of the inlet pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Osman et al. 2 investigated the relationship among the splicing strength, the air inlet pressure and the cross-section area of the splicing chamber through ANSYS software. Results showed that the splicing strength increases with the increase of inlet pressure first and then decreases.…”
mentioning
confidence: 99%
“…Osman et al. 2 investigated the relationship among the splicing strength, the air inlet pressure and the cross-section area of the splicing chamber through ANSYS software. Results showed that the splicing strength increases with the increase of inlet pressure first and then decreases.…”
mentioning
confidence: 99%
“…Xing and Ye 11 analyzed the characteristics of the airflow in different parts of a splicing chamber by adopting a commercial CFD software, FLUENT. By carrying out large eddy simulation of the flow field in splicing chambers with various structures, Osman et al 12 gained insight into the parameters that were significant to obtain good splicing characteristics. In our previous work, the movement of filaments during the splicing process was studied by the combination of high-speed photography and a threedimensional (3D) numerical model.…”
mentioning
confidence: 99%